Two-Dimensional Simulation Of Upper Sungai Langat Using HEC-HMS, HEC-RAS And RRI Model - Mohamad Faudzi, Siti Multazimah (2019)
Flood is one of the natural disasters occurring in Malaysia. Floods usually occur due to the overflow of water from the riverbanks which inundates the surrounding area. Hulu Langat district, located in Selangor was severely affected by floods. Sungai Langat is the main river flowing from Banjaran Titiwangsa into the Strait of Malacca with a length of approximately 141 km. The study area is focused on the upper Sungai Langat basin area where main cities such as Kajang, Bangi, Seri Kembangan and Dengkil are situated. These cities which are located at the downstream area of upper Sungai Langat were frequently inundated during heavy rainfall events. This scenario had caused a nuisance to the surrounding people of the inundated areas. Thus, HEC-HMS, HEC-RAS and RRI models were used to simulate the rainfall-runoff occurrences in the upper Sungai Langat basin. The objectives of this study are to (a) simulate the flood inundation in upper Sungai Langat using HEC-HMS and RRI models; (b) compare the results of HEC-HMS and RRI models based on discharge values and; (c) produce flood maps using HEC-RAS and RRI models. The rainfall and discharge data which were used as the input data for HEC-HMS and RRI models were provided by the DID. DEM data of 1 arc-second and 30 arc-second resolutions were used in the HEC-RAS and RRI models respectively. Simulation of five rainfall events using HEC-HMS and RRI model were conducted to calibrate particular parameters. The calibrated parameters were used to validate three rainfall events using HEC-HMS and RRI models. The graphs of observed versus simulated discharges were plotted to find the correlations between both data using the correlation coefficient,